PERTANGGUNGJAWABAN KLAUSULA EKSONERASI PADA PERUSAHAAN PENITIPAN JASA KENDARAAN BERDASARKAN PERATURAN WALIKOTA (PERWAL) KOTA SERANG NOMOR 21 TAHUN 2020 TENTANG PENYELENGGARAAN PERPARKIRAN - Herlambang, Fahmi; Aslami, Iron Fajrul; Safiulloh, Safiulloh (LPPM Universitas Bina Bangsa, 2024)
Parking management, apart from economic and business activities, is an activity that contains legal aspects where management needs to be regulated for the protection of the users and company. Parking management at Pasar Rau, Serang City, Banten Province, which is now called Rau Trade Center (RTC), is managed by PT Pesona Banten Persada with parking as one of its services, which refers to the legal basis of Serang Mayor Regulation Number 21 of 2020 concerning Parking Organisation, but in In practice, on the tickets obtained by consumers using the service, the management includes an Exoneration Clause, which is a clause stated in a contractual relationship in an effort to avoid providing an obligation, which gives rise to legal problems regarding liability for lost vehicles. The research method used in writing is normative with an empirical approach, sourced from data based on field data with the aim of comparing legal rules and facts in the field to obtain a legal solution for the community and consumers who use parking services